Identificação de redes gênicas de coexpressão e dos mecanismos regulatórios associados à composição mineral e qualidade de carne em bovinos - Diniz, Wellison Jarles da Silva (Universidade Federal de São Carlos, 2019)
Meat quality and mineral composition are complex traits genetically regulated. Growing evidence suggests that minerals play a central role in regulatory and physiological functions related to meat tenderness and fat deposition in cattle. Furthermore, miRNAs and genes have been identified as potential regulators of these traits. However, there is a lack of knowledge regarding the interplay among miRNA-gene expression-mineral metabolism in cattle. Thus, to explore regulatory pathways, candidate genes and miRNAs, and their relationships to muscle and mineral metabolism in Nelore steers, we integrated gene and miRNA expression data, eQTLs, mineral content, and meat quality traits based on coexpression networks. To this end, the muscle genome-wide expression profiles of mRNAs (n = 200) and miRNAs (n = 50), obtained by RNA-Seq, were used separately to construct co-expression networks using the WGCNA (Weighted gene co-expression network analysis) R package. Phenotypic data of macro (Ca, K, Mg, Na, P, S) and micro minerals (Co, Cr, Cu, Fe, Mn, Se, Zn), as well as meat quality (intramuscular fat, meat pH, and tenderness) were also integrated to identify gene/miRNAs modules associated to these traits. By clustering 11,996 genes and 343 miRNAs, we identified, based on a linear model, 15 and nine modules, respectively, associated with at least one trait (p < 0.05). We identified 82 potential candidate genes based on the module-phenotype association analysis. From the functional analysis, we identified as over-represented biological pathways related to energy and protein metabolism, such as AMPK, mTOR, insulin, and thyroid hormone. We also integrated the gene and miRNA modules, and pointed out 1,815 unique genes targets of 41 miRNAs. Among the minerals, Ca and Fe were strongly regulated, mainly by the miR-29 family. In addition to the pathways previously mentioned, the target genes functional over-representation analysis highlighted signaling pathways such as hypoxia-inducible factor 1, ferroptosis, and p53. Key genes involved in Fe homeostasis, such as transferrin receptor (TFRC), iron responsive element binding protein 2 (IREB2), and transferrin (TF) were identified, as well as those underlying lipid metabolism. Overall, there is a complex relationship between meat quality and mineral metabolism, as well as the fundamental role of miRNAs regulating target genes. Further studies are needed to investigate the effect of different levels of mineral supplementation in gene expression and meat quality traits.
Identification of co-expression gene networks and regulatory mechanisms related to mineral composition and meat quality in bovine
Keywords: Análise de Redes; Genômica Integrativa; Maciez da Carne; Metabolismo Mineral; Network analysis; Integrative genomics; Meat tenderness; Mineral metabolism; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS AGRARIAS::ZOOTECNIA::GENETICA E MELHORAMENTO DOS ANIMAIS DOMESTICOS